Client-centred practice in occupational therapy : a guide to implementation. - Sumsion, Thelma, ....-; Craik, Christine, ....-; Glossop, John, ....- (Edinburgh : Churchill Livingstone, 1999)
Contents: Interest in the use of a client-centred approach to practice hasdeveloped rapidly during the last decade and many occupational therapistsare now endeavouring to implement it. The principles of this approach arealso being introduced to students as part of their undergraduate studies.This text aims to provide a readable introduction to the theories ofclient-centred practice and to show how it may be applied to thetherapeutic management of different client groups. Client-Centred Practice in Occupational Therapy is written in a stylewhich is accessible to both students and practitioners. It demonstratesclearly how the concept of client-centred care may be usefullyincorporated into day to day occupational therapy practice.
Keywords: Ergotherapie -- Client-centered.; Ergotherapie -- Methodiek; Ergotherapie